(3GdfbhO hGdHfhcs - (3HWQS SGeQ(B, (3LdOIs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2007)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjIc WHjYI GdfbhO hhXGFagG,CfhGY GdfbhO,GdfXe GdfbOjI;GdEUOGQ GdfbOj,GdfXQjI GdfbOjI GdcdGSjcjI, GdfXQjI GdfbOjI GdMOjKI,GdHfhc GdJLGQjI,GdHfhc GdeQcRjI,COhGJ GdSjGSI GdfbOjI,eSJLOGJ GdYed GdeUQaj,GdJVNe(B. s
(3HjHdjhZQGajG U(B. 161 s
Keywords: (3Hfhcs; (3fbhOs